Who suffers from unemployment? The role of health and skills - Anton Nilsson (IZA Journal of Labor Policy, 2015)
Unemployment swings have distributional consequences if some groups are hit harder than others. We examine if the sensitivity to local unemployment rates varies by characteristics such as health, cognitive ability and non-cognitive ability. Data on these variables come from registers covering the entire Swedish population of males. We show that variations in the unemployment rate are associated with larger variations for those with poor health or with a low non-cognitive ability. This pattern is found both among young and older individuals. The employment of the lower-educated also varies more with variations in the unemployment rate, but only among younger workers.
Keywords: I10; J24; J31; E32; 330; Health; Cognitive ability; Non-cognitive ability; Education; Employment; Unemployment; Business fluctuations